Kyiv romanticism in the aspect of life-formation - Борзенко, Олександр Іванович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article investigates the influence of romanticism on «biographical stories» of famous participants of the Cyril and Methodius Brotherhood. The mechanism of formation of alternative biographies is considered. We have identified thematic complexes of vocation and destiny in the self-actualization of writers. The activities of the secret society were important symbolic attributes. They created an atmosphere of mystery, important for a romantic understanding of biographical stories. We paid particular attention to the disclosure of behavioral strategies and role situations. We also analyzed the literary masks chosen by the members of a secret society. We took into account the influence of the repressions of 1847 on the fate of the «Kiev conspirators». The concept of romantic overcoming real events, the actualization of a romantic act also became the subject of study. Aesthetically conditioned suicides of decent behavior have attracted our attention. The connection between romantic life and the context of Ukrainian national revival is determined.